Accounting Information System in Egg Trading Business with Consignment Sales Method - Handiyanto, Ramada Aji; Wicaksono, Soetam Rizky; Setiawan, Rudy (Jurnal Sistem Telekomunikasi Elektronika Sistem Kontrol Power Sistem dan Komputer, 2023)
UD Berkah Mutiara Telur is a company engaged in the sale and purchase of eggs. Because the company sells on consignment, wholesale, and retail, recording transactions that have been carried out using books and Microsoft Excel has become difficult because variations in sales cannot be recorded properly and the data becomes out of sync so that data differences often occur, especially on stock. goods, the amount of receivables, and the amount of debt that is not monitored. Therefore, companies need an accounting information system that can record the entire transaction process running in the company so that the data becomes integrated and facilitates data monitoring. The system was developed using the System Development Life Cycle (SDLC) method which consists of planning, analysis, design, implementation, testing, and maintenance stages. The system can assist companies in managing sales on consignment, wholesale, and retail, generate financial reports, and help monitor stock, accounts payable, and receivables.